2006
DOI: 10.1016/j.pain.2006.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Changes to somatosensory detection and pain thresholds following high frequency repetitive TMS of the motor cortex in individuals suffering from chronic pain

Abstract: Research has shown that transcranial magnetic stimulation (TMS) results in a transient reduction in the experience of chronic pain. The present research aimed to investigate whether a single session of high frequency TMS is able to change the sensory thresholds of individuals suffering from chronic pain. Detection and pain thresholds for cold and heat sensations were measured before and after 20Hz repetitive TMS (rTMS) administered over the motor cortex. A significant decrease in temperature for cold detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 47 publications
4
61
1
7
Order By: Relevance
“…Similar studies using a different technology (transcranial magnetic stimulation; TMS) suggest that stimulation of the motor cortex is associated with changes in heat and cold sensory thresholds as well as heat and cold pain thresholds. 8,22,31 Using tDCS, Bachmann et al 3 found that cathodal stimulation over the motor cortex significantly impacted cold sensory, mechanical sensory, and mechanical pain thresholds in the contralateral hand. Bachmann et al found no significant effects for cold pain thresholds, pressure pain thresholds, or wind-up pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar studies using a different technology (transcranial magnetic stimulation; TMS) suggest that stimulation of the motor cortex is associated with changes in heat and cold sensory thresholds as well as heat and cold pain thresholds. 8,22,31 Using tDCS, Bachmann et al 3 found that cathodal stimulation over the motor cortex significantly impacted cold sensory, mechanical sensory, and mechanical pain thresholds in the contralateral hand. Bachmann et al found no significant effects for cold pain thresholds, pressure pain thresholds, or wind-up pain.…”
Section: Discussionmentioning
confidence: 99%
“…In the real stimulation group, 46% of participants guessed correctly (X 2 = .004, P = .94, ns) and in the sham group 18% guessed correctly (X 2 [1] = 2.23, P = .14, ns). The average guess-confidence rating was 5.50 (SD = 3.10) in the real HD-tDCS group and 4.55 (SD = 2.16) in the sham group (t [22] = .86, P = .399, ns).…”
Section: Hd-tdcs Experience Tolerability and Mask Validitymentioning
confidence: 94%
See 1 more Smart Citation
“…1,8,9,[33][34][35][36] Generally, in these studies, clinically healthy participants were enlisted and were subjected to either ischemic muscle pain, 1 cold immersion, 33,36 capsaicin, 35 or laser-stimulated pain. 9,34 One study assessed whether sensory and pain thresholds were modifiable in patients with chronic back pain.…”
Section: Rtms In Experimentally Induced Painmentioning
confidence: 99%
“…Des données similaires ont été retrouvées chez des patients atteints de syndrome douloureux régional complexe de type I ayant reçu dix séances de SMTr à 10 Hz [41]. Johnson et al [17] ont évalué l'effet de la SMTr à 20 Hz chez des patients atteints de douleurs lombaires. Ils ont observé une réduction moyenne de 28 % de l'intensité douloureuse mesurée sur une EVA, qui était corrélée à un changement de la perception thermique au froid.…”
Section: Utilisation De La Smtr Pour Le Traitement Des Douleurs Non Nunclassified